Role of public research institutes in national innovation systems in industrialized countries: The cases of Fraunhofer, NIST, CSIRO, AIST, and ITRI - Intarakumnerd, Patarapong; Goto, Akira (Research Policy, 2018)
Public research institutes (PRIs) were established for many reasons including promoting defense related research and health related research. Helping domestic industries remain as one of the important missions for PRIs even when the countries have become industrialized and firms' technological capabilities are high. PRIs aim to upgrade existing industries, especially small and medium-sized enterprises (SMEs), as well as spearheading new ones. They can conduct research to solve today's problems in the existing industries and those of next-generation technologies which may lead to the creation of new industries. Moreover, the relationship between PRIs and firms and non-firm actors such as universities became more intense, open, horizontal, international, and long term. To reduce risk and uncertainty inherent in the research mentioned above, the intermediary roles of PRIs are becoming increasingly important. The emphasis and the ways that PRIs help industry change over time and vary across countries as they are an integral part of national innovation systems. This makes generalization difficult, but the experiences of five leading PRIs in Germany, Taiwan, Japan, Australia, and the United States shows that the balances between contract research vs. longer term research with its own initiative, mobility of researchers vs. retaining core researchers, and competitive grants and funds from industry vs. block grants from governments are important in keeping PRIs relevant to industry needs and maintaining research standards. These balances depend on the nature of the national innovation system in which they are embedded. The governance of PRIs is of particular importance to maintain proper balances.